Originally Posted by

**MathCrusader** My bad I forgot to write that it needs to be done using modular arithmetic. Considering that I was attempting to do it using modular arithmetic and I posted it under 'Number Theory', it's surprises that it wasn't evident how it's meant to be solved, but I digress.

So, how would we move on from:

$\displaystyle \begin{cases} 11x - 5y \underset{2}{\equiv} 7 & \Leftrightarrow \ \ x + y \underset{2}{\equiv} 1 \\9x + 10y \underset{2}{\equiv} -3 & \Leftrightarrow \ \ x \underset{2}{\equiv} 1 \end{cases}$